The power of conviction (Cultura Económica, 2019)
In this article, Pablo Grigoriu, PhD candidate in Economics at our University, criticizes some key points of the neoclassical model in economics. Opposing the “homo economicus” of the neoclassical rationality to the “human being” of personalism, the author considers the place of moral values and the objective dimension of man in the traditional econometric schemes. After an epistemological rupture between Economics and culture in economic thought, economists have focused solely on the subjective dimension of the person, considering only the utility. However, there are factors such as the moral conviction that have an important role in economic decisions and are not adaptable to a conventional instrumental rationality.
Keywords: formal limitations; informal limitations; incentive mechanism; morality